Benefits of Aerobic Exercise for Heart Health: Literature Review - Ria, Riya (Journal of Salutare, 2025)
Heart disease is one of the leading causes of death in the world, including in Indonesia, which is generally caused by an inactive lifestyle, unhealthy diet, and stress. One preventive effort that has proven effective is through physical activity such as aerobics. This study aims to examine the benefits of aerobics on heart health through a literature study method with a descriptive qualitative approach. Data were collected from various relevant national and international scientific journals over the past ten years. The results of the review show that aerobics can increase heart efficiency, lower blood pressure, improve blood lipid profiles, and increase VO2 max capacity. In addition, aerobics plays a role in weight control, improving psychological function, and reducing the risk of stress, all of which contribute to heart health. This activity is also considered safe and can be done by various age groups, including the elderly. However, low health literacy is a challenge in implementing aerobics widely. Therefore, ongoing education based on scientific evidence is needed to increase public awareness of the importance of exercise in preventing heart disease.